Quantum Algorithm for Multiplicative Linear Logic - Saraiva, Lorenzo; Haeusler, Edward Hermann; Costa, Vaston (Anais do Workshop Brasileiro de Lógica (WBL); 2023: Anais do IV Workshop Brasileiro de Lógica, 2023)
This paper describes a quantum algorithm for proof search in sequent calculus of a subset of Linear Logic using the Grover Search Algorithm. We briefly overview the Grover Search Algorithm and Linear Logic, show the detailed steps of the algorithm and then present the results obtained on quantum simulators.